Explaining equity gains in child survival in Bangladesh: scale, speed, and selectivity in health and development - Adams, Alayne M; Rabbani, Atonu; Ahmed, Shamim; Mahmood, Shehrin Shaila; Al-Sabir, Ahmed; Rashid, Sabina F; Evans, Timothy G (© 2013 The Lancet, 2017)
This review was published in The Lancet [© 2013 The Lancet] and the definite version is available at: http://www.thelancet.com/journals/lancet/article/PIIS0140-6736(13)62060-7/abstract